Sinonimia y metalenguaje - Real Torres, Carolina (2000)
The interdiction is a linguistic phenomenon which occurs mainly in the lexical-semantic level. In this field and among the euphemistic substitutes with a semantic basis, we find the synonyms and the metaphorical expressions which, in spite of their different nature, share a common link as they are both based on a relationship of similarity and they both contribute to meet all the expression needs in the language.
Keywords: Metáfora; Metonimia